The Legal Regulation of the Internal Security Forces in Iraqi Constitution and Laws - Omer, Shorsh Hassan; Shakir, Dalia Sherko (Journal of Legal and Political Studies, 2021)
The Iraqi Interior Security Forces have gone through several developments phases in Parallel with the general development of the country since its establishment. Prior to 2003, the Iraqi constitutions did not regulate interior forces through determining these forces and their compositions in detail rather they only regulated the declaration as state of emergency. Since the establishment of new Iraqi Constitution OF 2005, there have been reforms in regard to the interior forces from different perspectives including the structure of these forces, their authorities and their new types, however the Constitutions of 2005 took the similar path of the previous in leaving the matter unregulated by its provisions. The Constitution of 2005 did not regulate this matter precisely and in detail. These issues will be addressed through constitutional amendments which are considered very important points in federal systems.
Keywords: Iraqi Interior Security Force; Iraqi constitution,reforms; state of emergency; constitutional amendments